Epstein-Barr virus load in transplant patients: Early detection of post-transplant lymphoproliferative disorders - Fellner, María Dolores (2016)
Fil: Fellner, María Dolores. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.